Comprehensive approaches to expanding CRISPR biosensor applications beyond nucleic acid targets - Nandi I.; Verma J.; Prasad R.; Singh S.K.; Chandra P. (My University, 2025)
The CRISPR/Cas system has transformed molecular diagnostics due to its exceptional specificity and programmability. Initially designed for detecting nucleic acids, recent progress has expanded its use to include non-nucleic acid targets. This review offers an in-depth examination of recent innovations in CRISPR-based biosensing, focusing on proteins, heavy metals, toxins, and other metabolites. It highlights novel methods that incorporate antibodies, aptamers, and DNAzymes for detection. Key CRISPR biosensing techniques, such as target recognition, signal conversion, and amplification, are discussed within the context of biosensor design principles. The review also addresses the future potential and challenges of CRISPR-powered biosensors, suggesting areas for further development and improvement in biosensing technologies. © 2025 Elsevier B.V.